National and subnational burden of brain and central nervous system cancers in China and global from 1990 to 2021: results from the global burden of disease study 2021 - Shifan Tu; Xiaolu Huang; Xiaoxuan Fan; Yi Zhang; Lan Huang; Kai Li; Xinyue Wang; Yunpeng Gao; Xiaoping Zhao; Zhaoqun Feng (Archives of Public Health)
Abstract Background Primary central nervous system (CNS) cancers remain a leading global cause of mortality and morbidity. However, comparative analyses between China and global regions during the 1990–2021 period remain lacking in the existing literature.Leveraging data from the Global Burden of Disease Study 2021 (GBD 2021), this study addresses this gap by providing a comparison of primary CNS cancer trends in China and global regions from 1990 to 2021. Through systematic analysis of temporal trends in age- and sex-specific burdens of primary CNS cancers in China—including incidence, prevalence, mortality, and disability-adjusted life years (DALYs)—this study establishes a novel comparative framework aligned with global disease burden metrics. Leveraging the most recent data from the GBD 2021, we elucidate disparities in disease burden and evolving trends between China and global regions. These updated findings provide critical insights for optimizing resource allocation and informing tailored interventions. Methods Using open data from the GBD 2021 database, we analyzed characteristics of CNS cancer burden in China and globally from 1990 to 2021, including changes in incidence, prevalence, mortality, and DALYs.We employed Joinpoint regression analysis to calculate the average annual percentage change (AAPC) with 95% confidence intervals (95%CI), evaluating temporal trends in CNS cancer burden.A comparative analysis was conducted across multiple dimensions (age, sex, and time periods) to examine differences in CNS cancer burden between China and other world regions. Results From 1990 to 2021, the age-standardized incidence rate (ASIR) of CNS cancers in China increased from 4.69 to 6.12 per 100,000 population, while the global ASIR rose from 3.75 to 4.28 per 100,000.The age-standardized prevalence rate (ASPR) in China increased from 9.68 to 21.23 per 100,000, compared with a global increase from 8.66 to 12.01 per 100,000.China’s age-standardized mortality rate (ASMR) declined from 4.05 to 3.63 per 100,000, whereas the global ASMR showed a marginal increase from 3.04 to 3.06 per 100,000.The age-standardized DALY rate (ASDR) decreased from 174.36 to 134.15 per 100,000 in China, with a corresponding global decline from 119.88 to 107.91 per 100,000.The average annual percentage changes (AAPCs) were 0.86%, 2.53%, -0.34%, and − 0.87% for ASIR, ASPR, ASMR, and ASDR in China, respectively, compared with global AAPCs of 0.42%, 1.06%, 0.01%, and − 0.35%.Age and sex exhibited differential impacts on CNS cancer burden. Conclusions From 1990 to 2021, China experienced sustained increases in both ASIR and ASPR of CNS cancers, indicating a growing disease burden.The disease burden exhibited significant age and sex disparities: males showed higher ASIR, ASMR, and ASDR, whereas females had higher ASPR.Age-specific analysis revealed higher ASIR, ASPR, ASMR and ASDR among pediatric and elderly populations in China.Given China’s large population and accelerating aging demographics, CNS cancers remain a major public health challenge.We recommend developing targeted surveillance strategies for aging and high-risk populations, establishing a comprehensive “prevention-diagnosis-rehabilitation” management framework.This would facilitate a paradigm shift from passive treatment to proactive prevention, systematically alleviating the public health burden of CNS tumors.